Advances in visual methodology - Pink, Sarah. (Sage Publications, 2012)
"Sarah Pink draws together in a single volume a set of key writings on advances and explorations that sit at the innovative edge of theory and practice in contemporary visual research. Advances in Visual Methodology presents a critical engagement with interdisciplinary practice in the field of visual research and representation, examining the development of visual methodology as a field of interdisciplinary and post-disciplinary practice that spans scholarly and applied concerns. The book explores how new practice-based, theoretical and methodological engagements are developing and emerging in research practice; the impact new approaches are having on the types of knowledge visual research produces and critiques; the ways visual research intersect with new media; and the implications of this for social and cultural research, scholarship and intervention."--Publisher's website.